Unambiguous SAR Signal Reconstruction from Nonuniform Displaced Phase Center Sampling - Krieger, Gerhard; Gebert, Nicolas; Moreira, Alberto (IEEE Geoscience and Remote Sensing Letters, 2004)
The displaced phase center (DPC) technique will enable a wide-swath synthetic aperture radar (SAR) with high azimuth resolution. In a classic DPC system, the pulse repetition frequency (PRF) has to be chosen such that the SAR carrier moves just one half of its antenna length between subsequent radar pulses. Any deviation from this PRF will result in a nonuniform sampling of the synthetic aperture. This letter derives an innovative reconstruction algorithm and shows that an unambiguous reconstruction of a SAR signal is possible for nonuniform sampling of the synthetic aperture. This algorithm will also have great potential for multistatic satellite constellations as well as the dual receive antenna mode in Radarsat 2 and TerraSAR-X.
DLR Import::2019-04-02
Keywords: Azimuth ambiguities; Digital beamforming; Displaced phase center antenna (DPCA); High-resolution wide-swath SAR; Interferometry; Synthetic aperture radar (SAR)